The Effect of Open Unemployment Rate, Education Level, and Labor Force on Poverty in Indonesia 2018-2022 - Vika Rahmaningtyas; Happy Adianita (Yayasan Riset dan Pengembangan Intelektual, 2023)
Poverty is a common problem for all countries, both in developing and developed countries. Like other developing countries, Indonesia still faces problems related to poverty. In a period of five years, Indonesia's poor population has fluctuated, where in 2020 it experienced a fairly high increase due to the covid19 virus. Thus it is very important to conduct research on the circumstances that affect poverty. The purpose of conducting research in order to determine the effect of the Open Unemployment Rate (TPT), Education Level, and Labor on Poverty in Indonesia in 2018-2022. This type of quantitative research uses data from 34 provinces with observations from 2018-2022 obtained from the BPS website and journals to support this research. The tool used is Eviews12 through the Commond Effect Model (CEM) analysis technique. The results of the study explain that the Open Unemployment Rate has a negative but insignificant effect on poverty, the level of education has a negative and insignificant effect on poverty and labor has a significant negative effect on poverty. However, it simultaneously affects poverty. Adjusted R-Square is worth 39.0261% that the independent variables including open unemployment rate, education level and labor can be explained in the poverty variable while the remaining 60.9739% is explained in variables not included in this study.